ANALISIS KESESUAIAN RPP DENGAN PELAKSANAAN PEMBELAJARAN AKUNTANSI DASAR YANG MENGGUNAKAN KURIKULUM 2013 DI SMKN MANAJEMEN BISNIS KOTA PADANG - Rahmi Sartika; Dessi Susanti (Jurnal Ecogen, 2019)
This study aims to describe the suitability of the RPP with the Learning Implementation Process, the suitability of the RPP made by teachers with the 2013 Curriculum, and the obstacles faced by teachers in implementing the RPP. Data collection using, documentation, observation, interviews and then data were analyzed using qualitative descriptive methods. Based on the results of the analysis it is known that the percentage of completeness of the RPP components of Vocational High School Business Management in Padang with the Curriculum Component of the 2013 RPP is 97.01%, the percentage of the suitability of the RPP with the implementation of learning is 27.7%, 27.8%, 30.4%,36 , 2% and 41.7%. this means that the teacher is not competent in carrying out the lesson plans when implementing learning in the classroom. The obstacles faced by teachers are lack of time, IT like Infocus is also inadequate in schools and lack of source books.Keywords: learning implementation plan, learning implementation process, curriculum 2013